Converting round tendons to flat tendon constructs: does the preparation process have an influence on the structural properties? - Domnick, Christoph; Siebold, Rainer (Knee surgery, sports traumatology, arthroscopy, 2017)
Purpose: The structural properties of hamstring tendon grafts were evaluated in a porcine model, after processing it to a flat shape, to better replace or augment anatomic flat structures (e.g. ACL, MPFL or MCL).